2003
DOI: 10.1023/b:jarg.0000006705.46147.a2
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Factors Affecting the Success Rate of Frozen–Thawed Embryos

Abstract: Purpose : In recent years the infertile population applying for IVF treatments was changed and so the indications for performing intracellular sperm injection (ICSI). The aim of this study was to analyze predicting factors of our thawing cycles. Methods : From December 1998 to July 2001, 440 consecutive thawing cycles were performed. Patient characteristics were examined. The number of cryopreserved embryos, number of transferred embryos, the timing of cryopreservation (48 h vs.72 h), and embryo survival rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
(15 reference statements)
2
8
2
1
Order By: Relevance
“…Certain authors propose D + 2 of development as the optimum day for embryo cryopreservation and obtain a significantly higher pregnancy rates in this group of embryos compared to the ones that are cryopreserved on D + 3 [13,24]. Other authors have described significantly higher pregnancy rates in embryos cryopreserved on D + 3 compared to D + 2 [25,26]. Our findings do not show significant differences in the implantation rate according to the day on which cryopreservation takes place.…”
Section: Discussioncontrasting
confidence: 51%
“…Certain authors propose D + 2 of development as the optimum day for embryo cryopreservation and obtain a significantly higher pregnancy rates in this group of embryos compared to the ones that are cryopreserved on D + 3 [13,24]. Other authors have described significantly higher pregnancy rates in embryos cryopreserved on D + 3 compared to D + 2 [25,26]. Our findings do not show significant differences in the implantation rate according to the day on which cryopreservation takes place.…”
Section: Discussioncontrasting
confidence: 51%
“…The FET outcome and post-thaw embryo survival ability related to the day of cryopreservation have seen discrepant results with few data available on this specific topic (12,16). The post-thaw survival parameters in our study were strictly comparable whatever the day of embryo cryopreservation was, providing evidence that the timing of embryo cryopreservation had no effect on the post-thaw survival.…”
contrasting
confidence: 63%
“…Our data indicate that developmental stage and age of embryos at freezing affect to the outcome of ICSI-ET thawing cycles. Our ET and IR results are in agreement of others' observations who reported 27-34% clinical pregnancy and 12-16% implantation rate with blastocysts (13,14,19,25,26). Simon et al (1998), comparing the pregnancy rates of frozen embryos originating from tradional IVF and ICSI, found higher pregnancy rate after transferring frozen/thawed traditional IVF embryos (32.5% vs. 20%)(24).…”
Section: Discussionsupporting
confidence: 91%
“…Nowadays, ICSI is performed not only for male factor infertility but also in many cases of conventional IVF failure. Lahav- Baratz et al (2003) reported that the frozen/thawed ICSI-ET and IVF-ET cycles should be evaluated separately because not all the factors influencing the success rate in traditional IVF-ET cycles are valid in the ICSI-ET cycles (26). The retrospective analyses of conventional IVF-ET cycles indicated that age of patients, number and age (developmental stage) of transferred embryos affected to the pregnancy results.…”
Section: Discussionmentioning
confidence: 99%